A Rare Case of Vaccine-Induced Immune Thrombotic Thrombocytopenia After mRNA COVID Vaccine : Um Caso Raro de Trombocitopenia Trombótica Induzida pela Vacina Após uma Vacina de mRNA COVID - Correia, Francisca (2024)
Vaccine-induced immune thrombotic thrombocytopenia (VITT) is primarily a complication of adenoviral vector-based COVID-19 vaccination. Emerging data are consistent with the possibility that rare cases of VITT may be seen in the setting of an mRNA vaccine. We present a case of a 62-year-old man, admitted due to multiple arterial and venous thrombotic events with severe thrombocytopenia, coagulopathy and elevated D-dimer, some days after administration of mRNA COVID-19 vaccine. After the exclusion of other etiologies and in the presence of detectable antibodies against anti-PF4 (ELISA only), the diagnosis of VITT was made. The patient improved after starting treatment with intravenous immunoglobulin, methylprednisolone, and argatroban, followed by oral prednisolone and apixaban. Despite anticoagulation a progression of a deep vein thrombosis happened, and anticoagulation therapy was changed to unfractionated heparin and then to warfarin. Despite the guidelines, increasing knowledge of VITT pathogenesis suggests that heparin does not worsen the course of the disease.